(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study was conducted at Pangantucan Bukidnon Community College (PBCC) in the Philippines. The objective of the study is to determine the students' knowledge, attitudes, and digital literacy on digital mass media. The data were collected personally by the researcher from the 2nd-year and 3rd year students of Pangantucan, Bukidnon Community College. A total of 108 students served as respondents in the study. Frequency counts, Likert scales, and ranks were employed. Findings show that the primary devices used by the participants were phones(97.22%) with secondary devices being laptops. The average screen time spent by students in using mass media is four hours. The most accessed digital platforms are Facebook, YouTube, and TikTok, while the webpage from the state and universities is moderately utilized. Digital mass media were perceived by Students positively with a positive attitude on digital tools with high level of knowledge. The level of usage was moderate (overall mean = 2.97), with Facebook groups, YouTube tutorials and TikTok content being used the most for agricultural information. The sample was overwhelmingly male (53.21%) as are the demographics of the agricultural workforce nationally.Digital mass media was considered very useful in learning about agriculture by the students (with overall mean score 4.18) because it is relevant, convenient and can make learning more easy for complex topics. The attitudes expressed were overwhelmingly positive, with a strongly agree rating with an overall mean of 4.68, which means that digital media helps to increase involvement, motivation and independent learning. The overall mean of the knowledge level was also rated as high (3.88), which indicates students' ability to use digital tools for academic and agricultural activities, as well as evaluate information retrieved from the internet. The frequency of digital mass media exposure was also high (overall mean 3.48), with numerous uses across multiple platforms and seeking out agricultural information. Challenges faced by the students include rampant fake news, intermittent internet connection, and limited research on agriculture students’ digital self-efficacy.